(untitled) (Journal of Pakistan Orthopaedic Association, 2019)
ABSTRACT Objective: To determine the causes of delay in treating clubfoot in our set up. Methods: This descriptive study was conducted from October 2015 and December 2018 in Hayatabad Medical Complex and Mercy Teaching Hospital Peshawar. Parents of all the patients of club feet meeting the inclusion criteria were interviewed in person about the possible causes of delay in treatment. Data stored in proforma. Results: In our study parents of 46 patients with clubfeet were interviewed. Male patients were 27(58.7%) while female 19(41.3%). Age ranges from 01 to 05 years with mean age of 1.7 ± 2.12 years. Majority (82.6%,n=38) of the parents actually consulted a qualified doctor and started treatment for the deformity earlier, but were either inadequate or incorrect. About 27(58.7%) patients could not afford the treatment after being diagnosed and counseled for further treatment. Some (17.4%,n=8) children were truly neglected as 05(10.8%) of them were taken to bonesetters, while 03(6.5%) parents initially noticed the deformity but considered it untreatable. Conclusion: Inadequate or incorrect treatment and inability to afford proper treatment are the main causes of neglected clubfeet in our set up.